Transduction of γδ T cells with Baboon envelope pseudotyped lentiviral vector encoding chimeric antigen receptors for translational and clinical applications - Pinot, Lorraine; Saßor, Aylin; Möker, Nina; Zhang, Congcong; Verhoeyen, Els; Hidalgo, José Villacorta; Orentas, Rimas J. (Frontiers in Immunology, 2025)
γδ T cells represent a promising cell platform for adoptive cell therapy. Their natural anti-tumor reactivity and HLA-independent target cell recognition make them an attractive platform for allogeneic adoptive immunotherapy clinical interventions. Initial clinical trials exploring allogeneic γδ T-cell therapies have demonstrated encouraging safety profiles. However, their therapeutic efficacy, especially against solid tumors, remains limited. This highlights the need for further optimization of γδ T cell products to improve anti-tumor potency, such as the increased targeting induced by the expression of a chimeric antigen receptors (CAR). However, a critical challenge in the development of CAR-γδ T cell therapies has been optimizing transduction efficiency with standard vector formats allowing for optimal CAR transgene expression that then produces an optimal therapeutic product. Here we present an effective method for enhancing CAR transgene expression in γδ T cells using a Baboon-pseudotyped lentiviral vector (BaEV-LV), comparing it to the conventional vesicular-stomatitis-virus-G protein (VSV-G) LVs. BaEV-LV significantly enhanced the transduction efficiency of γδ T cells with CARs, while conserving the beneficial cell product composition and phenotype of untransduced γδ T cells. The γδ T cells transduced with BaEV-LV CARs demonstrated significantly enhanced cytotoxicity against B7H3-expressing tumor cells in both 2D and 3D in vitro models. Our findings represent a significant advancement in CAR-γδ T cell engineering, offering a promising new avenue for cancer immunotherapy that combines the unique properties of Vγ9Vδ2 T cells with the targeted specificity of CAR technology. This method is compatible with automated closed-system platforms such as the CliniMACS Prodigy®, facilitating Good Manufacturing Practice (GMP)-compliant production for clinical trials. This feature significantly enhances the translational potential of engineered γδ T cells, paving the way for the development of next-generation γδ T cell-based immunotherapies.